Meningkatkan Hasil Belajar Biologi Siswa SMA Melalui Pemanfaatan Lingkungan Sekolah Seabgai Sumber Belajar - Syam, Asrullah; Setiawati, Henny; Jafar, Jusmiati; Hasriyanti, Hasriyanti; Dianita, Ariyanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to determine the learning profile and analyze the influence of using the school environment as a learning resource on the biology learning outcomes of class X Science 2 students at SMA Negeri 5 Enrekang. The type of research used is Pre-Experimental. The design used is a one-group pretest-posttest design. The research population was class XI MIPA students, with a sample of class XI MIPA2 students, sampling was carried out by random sampling. Even Semester 2022/2023 Academic Year. Data collection was carried out by administering an initial test (Pretest) and a final test (Posttest). The results of the research show that previously biology learning was only carried out in the classroom using textbooks as a learning resource, but after the use of the school environment was implemented, student activity increased to become active and enthusiastic. Inferential statistical analysis shows that the use of the school environment has a significant influence on improving student learning outcomes. By utilizing the school environment as a learning resource, student learning outcomes increase significantly, especially in plant classification material. This is caused by students' interest and motivation being stimulated by new learning experiences. Therefore, it is recommended that teachers actively utilize the school environment in the learning process to improve student learning outcomes in biology learning.